Low carbohydrate and psychoeducational programs show promise for the treatment of ultra-processed food addiction: 12-month follow-up - Jen Unwin; Christine Delon; Heidi Giæver; Clarissa Kennedy; Clarissa Kennedy; Molly Painschab; Molly Painschab; Frida Sandin; Charlotte Schon Poulsen; David A. Wiss (Frontiers in Psychiatry)
The topic of ultra-processed food addiction has been the subject of many peer-reviewed publications. Although on average 14% of adults may meet the criteria for ultra-processed food addiction in prevalence studies, it is not a recognized clinical diagnosis, hence a lack of published evidence-based treatment protocols and outcome data. In 2022, we reported outcomes pre- and post-intervention from an online, real food-based, low-carbohydrate educational program with psychosocial support related to ultra-processed food addiction recovery. The intervention was delivered across three locations, offering a common approach. The programs comprised weekly online sessions for 10–14 weeks, followed by monthly support groups. The previously published data were outcomes relating to ultra-processed food addiction symptoms measured by the modified Yale Food Addiction Scale 2.0, ICD-10 symptoms of substance use disorder related to food (CRAVED), and mental well-being as measured by the short version of the Warwick Edinburgh Mental Wellbeing Scale, pre- and post-intervention. The current report focuses on the same cohort’s 6- and 12-month follow-up data. The 12-month follow-up data show significant, sustained improvement in ultra-processed food addiction symptoms and mental well-being. These data are the first long-term follow-up results to be published for a food addiction program. Research is now needed to evaluate and compare other long-term interventions for this impairing and increasingly prevalent biopsychosocial condition.